Perancangan Modul Tambahan Portal Media Interaksi Sivitas Universitas Brawijaya bagi Alumni Universitas Brawijaya menggunakan Design Thinking - Budi Iswanto; Herman Tolle; Retno Indah Rokhmawati (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2023)
Brawijaya University developed a web-based interaction media portal called Guyub UB, which functions as a social media that is expected to be a forum for the Brawijaya University community to interact with each other and share information. The design of additional modules was carried out in order to attract alumni to use the Guyub UB interaction media portal. The design process was carried out using design thinking. The design process resulted in 4 additional modules, namely a module to complete user identity data for user search and tracer study needs, a user search module based on user status, a module to send and view media and information on user personal conversations, and a module to view and publish articles, event information, and job information through Guyub UB. In the test process, 15 respondents who are alumni of Brawijaya University were tested, getting a score on the effectiveness aspect of 85.454%, on the efficiency aspect, on the overall relative efficiency score of 100%. In testing the satisfaction aspect, a score of 85, grade B, excellent category, and classified in the adjective acceptable. The results of User Experience Questionnaire (UEQ) testing obtained a score on the attractiveness aspect of 2.49 (excellent), the clarity aspect of 2.32 (excellent), the efficiency aspect of 2.27 (good), the accuracy aspect of 2.35 (excellent), the stimulation aspect of 2.33 (excellent), and on the novelty aspect of 2.20 (excellent).